Romanian Journal of Indian Studies No. 5 2021 - GLIGOR, Mihaela (Presa Universitară Clujeană, 2021)
India is a mixture of emotions, colours, feelings, music, happiness, sorrow, life and death, gods and people. India is an endless puzzle which each soul that meets its mystery tries to solve. India is infinite, just as untrammelled as the fascination that it produces in the others. India is an incredible rich culture, with a history of thousands of years. It saw the rise of various civilizations, religions, dynasties, human groups, cultures and arts. India has been presented and represented in many forms in literary discourses, arts and heritage symbols. But the country is so vast that there always remains an area to be explored. Moreover, there are many new things to be interpreted. Any discussion on anything belonging to India and its culture is incomplete without interdisciplinary dialogue between various cultural aspects and elements.